PEMANFAATAN SISTEM GAGASAN KOMUNITAS SKOUW SAE, KOTA JAYAPURA (The idea system within the Skouw Sae community, Jayapura City) - Usman, La (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2019)
The idea system within the Skouw Sae community, Muara Tami District, Jayapura City plays an important role in fulfilling their basic needs. This study analyzes what kind of ideas system is found in the society. The data were processed using qualitative analysis. The results of the study found three types of ideas systems. The first, which is sourced from the knowledge in culture, such as: the knowledge that comes from the traditional house of tangfa, the position of the land in society, the work behavior, the money as the symbol of the head payment, the work behavior, the money as the symbol of the head payment, Hoo as a symbol of the regulation of natural resource utilization, prohibition of liquor, arisan education as a behavior support the completion of higher education, beads and money as a symbol of dowry, behavior in kinship, shamanism and the symbol of village administration. Secondly, which is based on beliefs and religions, such as: order or kati as a symbol of belief and parade of Easter and Christmas torches as a religious behavior. Third, sourced from sports, arts and ceremonies, such as sports, bajo dance, wo and mandep as a symbol of art and ceremonial behavior around the circle of life. ABSTRAKSistem gagasan dalam komunitas Skouw Sae, Distrik Muara Tami, Kota Jayapura memegang peranan penting dalam memenuhi kebutuhan dasar mereka. Penelitian ini menganalisis apa saja sistem gagasan yang terdapat pada masyarakat tersebut. Data diolah menggunakan analisis kualitatif. Hasil penelitian menemukan tiga jenis sistem gagasan. Pertama, yang bersumber pada pengetahuan dalam budaya, seperti: pengetahuan yang bersumber pada rumah adat tangfa, kedudukan tanah dalam masyarakat, perilaku kerja, uang sebagai simbol pembayaran kepala, perilaku kerja, uang sebagai simbol pembayaran kepala, Hoo sebagai simbol pengaturan pemanfaatan sumber daya alam, pelarangan minuman keras, arisan pendidikan sebagai perilaku mendukung penyelesaian pendidikan tinggi, manik-manik dan uang sebagai simbol mas kawin, perilaku dalam kekerabatan, perdukunan serta simbol pemerintahan kampung. Kedua, yang bersumber pada kepercayaan dan agama, seperti: tata atau kati sebagai simbol kepercayaan serta pawai obor Paskah dan Natal sebagai perilaku keagamaan. Ketiga, yang bersumber pada olah raga, kesenian dan upacara, seperti olah raga, tarian bajo, wo serta mandep sebagai simbol kesenian serta perilaku upacara sekitar lingkaran hidup.